FENOMENA HIBRIDITAS DALAM NOVEL 1890 KARYA AYU DEWI: POSTKOLONIAL HOMI K. BHABHA - Sakti M, Reztu Dwi; Nensilianti, Nensilianti; Saguni, Suarni Syam (Fakultas Bahasa dan Sastra Indoensia, 2026)
This study aims to examine the phenomenon of hybridity in Ayu Dewi's 1890 novel using Homi K. Bhabha's postcolonial concept. This study uses a descriptive qualitative method through text content analysis. Data collection was conducted through thorough reading and recording of relevant quotations, while data analysis used the Miles and Huberman model (reduction, presentation, conclusion drawing). The results of the study show the phenomenon of hybridity that gives rise to a new identity as a result of the mixing of colonial and local cultures. This phenomenon appears in three forms: linguistic hybridity (the use of Dutch and Malay), lifestyle hybridity (the adoption of European lifestyles), and character identity hybridity (such as Pamungkas and Utari). Hybridity functions as a mechanism for negotiating power, a form of resistance, and an attempt to build social mobility for colonized subjects.